Legal Aspect of State and Local Borrowing - Plotnikova, K. O. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the article is devoted to the consideration and improvement of the issue of budget borrowing. A detailed analysis of budget borrowing at the state and local levels. On the basis of a study of legislation and scientific literature, the structure of public debt and the use of a loan in budgetary activity are determined. Proposed effective ways to resolve the financial problems of the regions.